The first step of polycyclic aromatic hydrocarbon growth – A case study of hydrogen abstractions by H, OH, and CH3 radical - Reizer Edina; Tokaji György Marcell; Marcin Palusiak; Viskolcz Béla; Bela Fiser; Фішер Бейло; Fiser Béla (Elsevier, 2024)
Abstract. Polycyclic aromatic hydrocarbons (PAHs) represent a severe concern due to their detrimental effects on the environment and human health. These molecules can grow to larger and more toxic compounds via different reaction mechanisms which mostly begin with a radical formation. Since PAHs are fused benzene rings with hydrogens on their edges, radical formation and thus, the activation of the structure is achieved by the removal of one of these hydrogens. Hydrogen abstraction reactions were studied at previously determined potential re action initiation points of 10 parent PAHs. The ωB97XD/6–31 + G(d,p) level of theory was found to be suitable to compute the hydrogen abstraction reactions where hydrogen ( • H), hydroxyl ( • OH), and methyl radicals ( • CH3) were reaction partners of PAHs. Quantum theory of atoms in molecules (QTAIM) analysis was also carried out and the electron density of bond critical points and activation energy of the hydrogen abstaction correlation was found.
https://www.sciencedirect.com/science/article/pii/S2210271X24000690?via%3Dihub
Editorial board: https://www.sciencedirect.com/journal/computational-and-theoretical-chemistry/about/editorial-board
Contents: https://www.sciencedirect.com/journal/computational-and-theoretical-chemistry/vol/1234/suppl/C
Keywords: Reaction initiation; Benzo(a)pyrene; PAH; Electron density; QTAIM